Prediction of Vitamin A Stores in Young Children Provides Insights into the Adequacy of Current Dietary Reference Intakes. Issue 8 (13th July 2020) - Ford, Jennifer Lynn; Lopez-Teros, Veronica
ABSTRACT: Background: Limited data were available in infants and children when vitamin A (VA) DRIs were established; recommendations were developed based on average breast milk VA intake and extrapolation of data from adults. Objectives: Our objective was to evaluate whether DRIs and reported intakes, with and without VA from intervention programs, would be sufficient to develop adequate VA stores from birth to age 5 y in Bangladeshi, Filipino, Guatemalan, and Mexican children. Methods: A mathematical relationship was established, defined by a series of equations, to predict VA total body stores (TBS) as a function of age based on VA intake and utilization. TBS calculated using reported VA intakes, with and without additional VA from intervention programs, were compared to those predicted using DRIs (specifically, Adequate Intake and RDA). Liver VA concentrations were also estimated. Results: Our predictions showed that for these 4 groups, DRIs were sufficient to attain liver VA concentrations >0.07 μmol/g by 1 wk of age and sustain positive VA balance for 5 y. Using reported intakes, which were lowest in Bangladeshis from 1 y on and highest in Guatemalans, predicted VA stores in Bangladeshi and Filipino children increased until ∼2–3 y, then TBS stabilized and liver VA concentrations decreased with age. When VA interventions were included, stores exceeded those predicted using DRIs by 12–18 mo. In contrast, reported intakes alone in Guatemalan and Mexican children resulted in VA stores that surpassed those calculated using DRIs. For all populations, reported intakes were sufficient to build liver concentrations >0.07 μmol/g by 3 mo. Conclusions: Although more information is needed to better define dietary VA requirements in children, our results suggest that for an average, generally healthy child in a low- or middle-income country, current DRIs are sufficient to maintain positive VA balance during the first 5 y of life.